Characterization of Crack Tip Mechanical Field of Inhomogeneous Materials in Welded Joints by USDFLD Subroutine. (30th September 2022) - Bi, Yueqi; Yuan, Xiaoming; Hao, MingRui; Li, Daming; Wang, Shuai; Xue, He
Abstract : The unevenly distributed mechanical properties of welded joints are one of the important factors, which affect welded joints' safety seriously. The user-defined field (USDFLD) subroutine in ABAQUS finite element software can introduce variable-dependent material properties. This method can define inhomogeneous materials whose mechanical parameters depend on spatial coordinates and can be used to characterize the uneven mechanical properties of heat-affected zone and fusion zone. By establishing the static crack finite element model of welded joint with continuous change in yield strength, the sudden change in mechanical field in the numerical simulation process of sandwich structure model is eliminated. Compared with the existing numerical simulation methods of local mechanical heterogeneity of welded joints, this method provides a method to realize the structural integrity evaluation of welded joints.